PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KERJASAMA TIM DAN KINERJA KARYAWAN PADA PT ANGKASA PURA II (PERSERO) KANTOR CABANG BANDAR UDARA SULTAN SYARIF KASIM II PEKANBARU - Heru Prianto Heru Prianto; Marzoliina Marzoliina; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted at PT. Angkasa Pura II of Sultan Syarif Kasim II Pekanbaru Airport branch office. Pupulates totaling 240 employees and the number of samplers done by doing the slovin formula, which is divided into 5% by 150 employees. Primary data was collected by questionnaire as an instrument to prove the result of research, to test the hypothesis in this research is to use path analysis with SPSS program assistance selected sampling technique (150 people) employees at PT Angkasa Pura II (parsero) Sharif Kasim II Pekanbaru. The result of research shows that: 1) there was positive and significant influence of organizational culture on employee performance at PT Angkasa Pura II (parsero) of Syarif Kasim II Pekanbaru airport branch, 2) there was positive and significant influence of compensation on employee performance at PT Angkasa Pura II (parsero) of Syarif Kasim II Pekanbaru airport branch office, 3) there was positive and significant influence of team cooperation on employee performance at PT Angkasa Pura II (parsero) of Syarif Kasim II Pekanbaru, 4) there was positive influence and significant organizational culture on employee performance through teamwork at PT Angkasa Pura II (parsero) of Syarif Kasim II Pekanbaru airport branch office, 5) there was a positive and significant influence of compensation on employee performance through teamwork at PT Angkasa Pura II (parsero) the branch of Sultan Syarif Kasim II Pekanbaru airport.Keywords : Organizational Culture, Compensation, Teamwork, and Employee Performance